2022
DOI: 10.48550/arxiv.2203.00037
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Fluid-structure interaction of a bio-inspired passively deployable flap for lift enhancement

Abstract: Birds have a remarkable ability to perform complex maneuvers at post-stall angles of attack such as landing, take-off, hovering and perching. The passive deployment of self-actuating covert feathers in response to unsteady flow separation while performing such maneuvers provides a passive, adaptive flow control paradigm for these aerodynamic capabilities. Most studies involving covert-feathers-inspired passive flow control have modeled the feathers as a rigidly attached or a freely moving flap on a wing. A fla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Researchers showed that suction, or upperwing, covert-inspired flaps increase post-stall lift by enabling the suction side to maintain lower pressure through the pressure dam effect. Further, covert-inspired flaps decrease separation propagation on the upper surface, improving the wing resistance to stall [9][10][11][12][13][14][15][16][17][18]. However, despite the number of engineering studies on covert-inspired flaps and bird flight observations indicating that the coverts in nature deploy simultaneously on the upper and under wings [5], prior work mainly studied the suction (upper) side coverts deflected alone [9,10] or the pressure (lower) side, coverts deflected alone [16].…”
Section: Introductionmentioning
confidence: 99%
“…Researchers showed that suction, or upperwing, covert-inspired flaps increase post-stall lift by enabling the suction side to maintain lower pressure through the pressure dam effect. Further, covert-inspired flaps decrease separation propagation on the upper surface, improving the wing resistance to stall [9][10][11][12][13][14][15][16][17][18]. However, despite the number of engineering studies on covert-inspired flaps and bird flight observations indicating that the coverts in nature deploy simultaneously on the upper and under wings [5], prior work mainly studied the suction (upper) side coverts deflected alone [9,10] or the pressure (lower) side, coverts deflected alone [16].…”
Section: Introductionmentioning
confidence: 99%